Validity Curry Strengthened. (25th November 2013) - Shapiro, Lionel
<x xml:space="preserve">Abstract</x> Several authors have argued that a version of Curry's paradox involving validity motivates rejecting the structural rule of contraction. This paper criticizes two recently suggested alternative responses to "validity Curry." There are three salient stages in a validity Curry derivation. Rejecting contraction blocks the first, while the alternative responses focus on the second and third. I show that a distinguishing feature of validity Curry, as contrasted with more familiar forms of Curry's paradox, is that paradox arises already at the first stage. Accordingly, blocking the second or third stages won't suffice for resolving the paradox.